Myxomycetes in ecotopes and plant communities of Dunais’ky biosphere reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Species composition and distribution of myxomycetes were studied in various ecotopes and plant communities of Dunais’ky biosphere reserve. 16 species were found in forest (pine, willow, poplar and mixed), psammophytic and inundated communities. Fuligo septica (L.) F.H. Wigg. was recognized as the most wide spread species in forest communities, especially in pine plantations of Pinus pallasiana D. Don. Tubulifera arachnoidea Jacq. was revealed in poplar, Lamproderma ovoideum Meyl and Reticularia olivacea (Ehrenb.) Fr. – in willow forests only. In psammophytic communities with Elaeagnus angustifolia L., Artemisia scoparia Waldst. et Kit. and Leymus sabulosus (M. Bieb.) Tzvelev at the sand beaches of the Black Sea gulfs, Badhamia melanospora Speg., Ceratiomyxa fruticulosa (O.F. Müll.) T. Macbr., Physarum cinereum (Batsch) Pers., Ph. pusillum (Berk. et M.A. Curtis) G. Lister were collected once only.
Keywords: myxomycetes, Dunais’ky biosphere reserve, Ukraine.